Psychrotolerant and psychrophilic fungi fermentation: great potential for pharmaceutical exploration through natural sources / Sadia Sultan - Sultan, Sadia (Faculty of Pharmacy, 2024)
Natural products account for 60% of the total market, making them a major source of drug discovery. Some of these are sourced from the cultivation of microorganisms. This approach started with Fleming’ s serendipitous discovery of penicillin from the filamentous fungus, Penicillium notatum in 1929. His findings have raised the intensive investigation of nature as a source of novel bioactive agents. The broad chemical diversity of natural products, in addition to their strong correlation to biological functionality, is the justification for the necessity to constantly nurture natural products in today’ s discovery efforts.